2010
DOI: 10.2174/1874294701004010007
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of a Constitutive Lysophosphatidic Acid Acyltransferase 2 (LPAT2) Gene from Tropaeolum majus L~!2009-07-22~!2009-09-25~!2010-03-12~!

Abstract: The cloning and characterization of a lyso-phosphatidic acid acyltransferase (LPAT2; EC 2.3.1.51) from Tropaeolum majus from a 20,000 EST collection is described. The 1358 bp TmLPAT2 gene encodes a 42.6 kD polypeptide; the primary sequence has a membrane bound O-acyltransferase, MBOAT, Box I motif, and Boxes II, III and IV typical of LPATs from various species. Unlike many LPAT2s, the gene was constitutively expressed in all tissues. The TmLPAT2 functionality was confirmed by expression in a yeast LPAT deletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…) are increased in LPAAT‐OE. We do not believe that the changes found in DAG, PC and TAG were due to the substrate preference of the nasturtium enzyme per se , as this enzyme uses palmitoyl‐CoA and oleoyl‐CoA equally, as judged by specificity measurements (Taylor et al ., ) and the oilseed rape LPAAT was also shown to use these substrates at equivalent rates in a selectivity assay (Berneth & Frentzen, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…) are increased in LPAAT‐OE. We do not believe that the changes found in DAG, PC and TAG were due to the substrate preference of the nasturtium enzyme per se , as this enzyme uses palmitoyl‐CoA and oleoyl‐CoA equally, as judged by specificity measurements (Taylor et al ., ) and the oilseed rape LPAAT was also shown to use these substrates at equivalent rates in a selectivity assay (Berneth & Frentzen, ).…”
Section: Discussionmentioning
confidence: 99%
“…The construct used to produce overexpressing lines of B. napus was derived from a nasturtium (Tropaeolum majus) LPAAT gene New Phytologist (Taylor et al, 2010) whose activity was confirmed by complementation of a LPAAT deletion (SLC1 À ) mutant and has been shown to utilise 16:0-CoA and 18:1-CoA with about equal efficiency (Taylor et al, 2010). The details of the construct are shown in Fig.…”
Section: Production and Selection Of Lpaat Overexpressing Linesmentioning
confidence: 99%
“…We have generated a collection of 20 000 ESTs from a library of subtracted developing nasturtium embryo cDNAs, which we will continue to ‘mine’ to isolate key genes to effect trierucin synthesis in B. carinata. To this end, we recently cloned and characterized an LPAT2 from nasturtium ( TmLPAT2 ) that will catalyze the synthesis of dierucoyl PA in the Kennedy pathway 107. Current experiments underway will re‐transform the Crambe KCS + RNAi FAD2 dual transgene B. carinata line with the TmLPAT2 to try to produce B. carinata prototypes with 70% erucic acid or better.…”
Section: Case Studies In the Application Of Genetic Engineering To Enmentioning
confidence: 99%
“…Also, the overexpression of LPAATs increased seed oil content, thus reinforcing the utility of LPAAT genes as valuable biotechnological tools. Consequently, LPAAT homologs have been cloned from poached eggplant ( Limnanthes douglasii ) [ 22 ], A. thaliana [ 23 ], rapeseed [ 24 ], coconut [ 19 ], corn ( Zea mays ) [ 25 ], Indian cress ( Tropaeolum majus ) [ 26 ], Java olives ( Sterculia foetida ) [ 27 ], and castor [ 20 ]. The overexpression of a LPAAT gene from the SLCl-1 mutant yeast stain in A. thaliana and B. napus increased the incorporation of long-chain fatty acids into the sn -2 position of TAGs, leading to an increase in seed oil content by 8–48% [ 28 ].…”
Section: Introductionmentioning
confidence: 99%